Last man off : a true story of disaster and survival on the Antarctic seas - Lewis, Matt, 1974- (New York, New York : Plume, 2015)
"On June 6, 1998, twenty-three-year-old Matt Lewis had just started his dream job as a scientific observer aboard a deep-sea fishing boat in the waters off Antarctica. As the crew haul in the line for the day, a storm begins to brew. When the captain vanishes and they are forced to abandon ship, Lewis leads the escape onto three life rafts, where the battle for survival begins"--
Author's Note -- Crew List: MFV Sudur Havid -- Glossary -- Boat Plans and Maps -- Prologue: 18:30, Saturday, 6 June 1998 -- PART I. ESCAPE -- PART II. TROUBLE -- PART III. ADRIFT -- PART IV. DELIVERANCE -- Epilogue -- Afterword -- Report of the Court of Marine Inquiry : The Sinking of the MFV Sudurhavid
"Originally published in Great Britain by Viking, 2014"-- Title page verso
Includes bibliographical references (page 230)
Keywords: Lewis, Matt, -- 1974-; Sudur Havid (Fishing boat); Shipwrecks -- Antarctic Ocean; Survival at sea -- Antarctic Ocean; Severe storms -- Antarctic Ocean; Rescues -- Antarctic Ocean; BIOGRAPHY & AUTOBIOGRAPHY / Adventurers & Explorers; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs